2017
DOI: 10.1111/ijfs.13697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prebiotic potential of five kiwifruit cultivars after simulated gastrointestinal digestion and fermentation with human faecal bacteria

Abstract: Summary We studied the in vitro prebiotic potential of five different cultivars of kiwifruit including the green‐fleshed ‘Hayward’ and ‘Zesh004’ and the gold‐fleshed ‘Hort16A’, ‘Zesy002’ and ‘Zesy003’. The kiwifruit (25 g fresh weight equivalent) were subjected to simulated gastrointestinal digestion before fermentation for 16 h with faecal microbiota from ten individual donors. Microbial metabolites including lactate were quantified while changes in microbiome composition were determined by 16S rRNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The fruit were sliced and coarsely blended to a puree. Then 50 g puree aliquots were subjected to a gastrointestinal digestion and fermentation protocol, as previously described [ 30 ]. Inulin and water were included as controls.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fruit were sliced and coarsely blended to a puree. Then 50 g puree aliquots were subjected to a gastrointestinal digestion and fermentation protocol, as previously described [ 30 ]. Inulin and water were included as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The feces, required for the fermentation, were obtained from four healthy donors who had not taken antibiotics for the last 3 months, with approval from the Central Health and Disabilities Ethics Committee, New Zealand (13/CEN/144, approved on 11 October 2013). Samples were processed within 30 min of voiding, and blended in chilled pre-reduced glycerol-buffered saline (10 mM phosphate, 150 mM NaCl, 10% v/v glycerol, 0.05% w/v cysteine, pH 7.2) to 20% fecal slurry stocks and stored at −80 °C, as described previously [ 30 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SCFA production is often attributed exclusively to the fermentation of dietary fibre and prebiotics. However, an in vitro study using a simulated intestinal ecosystem found that SCFA production correlated with both the total fibre content and a range of polyphenolic compounds present in kiwifruit (Parkar et al ).…”
Section: Sources Of Prebioticsmentioning
confidence: 99%